COALBED METHANE POTENTIAL AND COAL CHARACTERISTICS IN MUARA LAKITAN AREA, SOUTH SUMATRA - Muhammad Heri Hermiyanto; R. Setiawan (Pusat Survei Geologi, 2010)
A research on Coal Bed Methane (CBM) of the Muaraenim Formation has been conducted in the Muara Lakitan area. Megascopically, the coal lithotype varies from dull to bright banded, with black – brownish black and brownish to black streaks, brittle – friable, dull-greasy luster, even-uneven, dirty on fingers, with resin patch and striation, dirt bands (clay/mud layers), pyrite striation, and pore structures. The coal quality, gained from geochemical analysis, indicates that its ash content ranges between 1.22% and 2.47%, total sulphur content is from 0.15% to 0.3 %, and the volatile matter of 38.02% - 40.81%. The coal is dominated by vitrinite (73.6 – 85.8 %), with minor amount of exinite (1.4 – 4.0 %), inertinite (4.2 – 21 % ) and mineral matter (2.4 – 8.2 %). Vitrinite reflectance, varies from 0.44% to 0.45 %, tends to indicate a sub-bituminous to high volatile bituminous-A coal rank. Kaolinite clays are the most prominent mineral matter within all coal samples analyzed, although the clay textures show irregular shapes. Iron oxides are also present in several samples. Microcleats found within the coals are mostly open, and are rarely filled by clay minerals. Based on Barbara/Winter diagram, the methane gas content in the studied area ranges from 0.57 m3/t – 1.70 m3/t = 20.44 scf/t – 60.96 scf/t. The total reserve of gas within six coal seams in the studied area is 15.524,28 scf.Keywords : Coal Bed Methane (CBM), Muaraenim Formation, Muara Lakitan